A Descriptive Study On Teaching Speaking At The Eighth Grade For Excellent Program Of MTS N 1 Surakarta In 2013 / 2014 Academic Year - Rahmi, Zulhida; , Drs. Djoko Srijono, M.Hum; , Nur Hidayat, M.Pd (2014)
This research aims at describing the implementation of teaching speaking at the eight grade for excellent program of MTs N 1 Surakarta in 2013/2014 academic year, the methods used by the teacher, the techniques used by the teacher, the problems faced by the teacher and the students, and the strategies implemented by the teacher to overcome the problems. The researcher collects the data by observing the English class and conducting an interview with the teacher and the students. The data include syllabus, speaking material, field notes, questionnaire, and interview scripts. The methods of collecting the data are observation, interview and analyzing documents. In analysing data the writer applied descriptive qualitative research consisting of data reduction, data display, and drawing conclusion. The result of the research shows that: 1) the objectives of teaching speaking in excellent program of MTs N 1 Surakarta are to build the students communicative competence in speaking English and the students have to master all English language skill namely speaking, listening, reading, and writing, 2) the methods used by the teacher in teaching speaking of excellent program are Direct Method (DM), Communicative Language Teaching (CLT), and Grammar Translation Method (GTM), 3) the techniques used by the teacher in teaching speaking are cooperative learning and task-based learning. 4) the problem faced by the teacher in teaching speaking are the teacher's difficulties to manage the students and the teacher's difficulties to manage time in teaching, 5) the problem faced by the students in teaching speaking are the different capability to receive the material and the students' low motivation in learning speaking English, 6) the teacher strategies to solve the problems are the teacher gives more motivation to the students, the teacher uses creative and innovative material, the teacher uses some methods and techniques in his teaching-learning process.